High strain rate properties of soft polymeric and biological materials - Graham, A (2023)
Accurate characterisation of the response of low modulus materials to applied deformation at high frequencies, or strain rates, is of significance in many industrial or scientific settings, in particular when considering personal protective equipment. However, because of the low speed of sound in these materials, producing accurate measurements of material constitutive properties, and separating these from specimen structural response, can be challenging. This report presents research on the development and use of a novel methodology for the mechanical characterisation of ultra-soft biological tissues and polymers at high frequencies. The core development is a novel apparatus for high rate characterisation of soft materials under shear loading. This apparatus and methodology has been successfully used to characterise silicone based elastomers, agarose gel and brain tissue at frequencies of over 1 kHz. Firstly, the apparatus was designed, modelled and implemented, with extensive validation data obtained from a commercial silicone elastomer. The apparatus was then used in conjunction with traditional rheometry to characterise a PolyDiMethylSiloxane (PDMS) polymer, and to show that the mechanical properties can be tuned over a wide range of both stiffnesses and frequencies, by varying the ratio of crosslinker when curing the PDMS, from hundreds of Pa up to several MPa. Further experiments were then performed on an agarose gel and brain tissue. Again, it was shown that the properties of the agarose could be modified by changing the composition. Further, the ability of the measurement system to examine spatially varying properties was confirmed. This is relevant to biological tissues, and also allows for more efficient data gathering, as multiple material types can be characterised in a single experiment. Both PDMS and agarose hydrogels are commonly used as simulants for biological tissues, however there is a paucity of data in the literature about the high frequency behaviour of these materials. This gap in the literature is being closed by this research. The ultimate aim of this research was to characterise brain tissue. Porcine brain tissue obtained from a local butcher has been characterised over a wide range of frequencies at two temperatures. A key enabling technology for the experiments was the Virtual Fields Method (VFM), which is used as a means to extract quantitative information about stresses inside a specimen from full-field acceleration data. A side project was performed to develop a method of characterising the large strain behaviour of a material over a wide range of stress states and strain rates using a single test. This is achieved via the use of the VFM, applied to a T shaped specimen designed to develop heterogeneous stress states during the test. This method has been validated over a range of strain rates and temperatures on two materials, 1000 series Aluminium and Polycarbonate with PDMS crosslinker. The Aluminium material was selected as it exhibits almost perfect elasto-plastic behaviour, with a large strain to failure. In contrast, the polymeric material demonstrates complex post-yield behaviour. Here, the VFM was shown to be a superior analysis method, even when conducted on data obtained from traditional uniaxial tensile tests. Unlike traditional analysis methods, the VFM was capable of measuring local material behaviour, and separating geometric effects and material behaviour on the global behaviour of the sample. This allowed for more accurate characterisation of the material, using fewer tests. This advantage was further increased when using the T specimens. Key contributions of this thesis are therefore the development of two novel test methodologies with wide applicability to measure the mechanical response of low and high modulus materials. The high rate shear testing apparatus and methodology characterises the full-field mechanical properties of soft materials over a wide range of frequencies, while the T test methodology is capable of characterising stiff engineering polymers and metals accurately and repeatably using far fewer tests than would be required under traditional engineering test methodologies. These provide data that would not be possible to obtain using traditional engineering test methodologys. A second contribution is the generation of novel high rate data on low modulus polymers and brain tissue. In preparation for future projects on this topic, a second high strain rate characterisation methodology, for volumetric (compressive) testing was developed in Finite Element code. It is shown that this is, in principle, a viable method for soft material characterisation; however, it could not be implemented in this thesis as it requires high speed imaging that is just out of reach of current technologies.